2020
DOI: 10.3390/coatings10100922
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Neodymium Element on the Crater Structure Formed on Al-17.5Si Alloy Surface Processed by High-Current Pulsed Electron Beam

Abstract: The effect of neodymium element on the elimination of crater structures on the surface of Al-17.5Si metallic materials processed by high-current pulsed electron beam was investigated in this study. Field emission scanning electron microscopy analysis indicated that the grain sizes of Al-17.5Si metallic materials were reduced and craters were removed from surfaces of the processed Al-17.5Si metallic material after addition of Nd. This can be attributed to the efficient transfer of heat accumulated in rich-silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition, a compact and stable passivation film of alumina is formed in the modified surface layer because of the presence of metastable structures (e.g., nanocrystalline structure), thus improving the anticorrosion property of the alloy surface. Therefore, the combined effects of the grain refinement and the microcrack elimination contribute to the improved anticorrosion property of the alloy surface [1,42].…”
Section: Corrosion Analysismentioning
confidence: 99%
“…In addition, a compact and stable passivation film of alumina is formed in the modified surface layer because of the presence of metastable structures (e.g., nanocrystalline structure), thus improving the anticorrosion property of the alloy surface. Therefore, the combined effects of the grain refinement and the microcrack elimination contribute to the improved anticorrosion property of the alloy surface [1,42].…”
Section: Corrosion Analysismentioning
confidence: 99%
“…The addition of Nd removes the craters that degrade friction performance [19]. Rare earths can purify a material, reduce the number of casting defects and lower the surface roughness of the material.…”
Section: Tribological Propertiesmentioning
confidence: 99%
“…As a high-density energy source, HCPBE can achieve energy deposition on the material surface in a short time, irradiating the metal surface for rapid heating and cooling [11][12][13][14][15]. According to the literature, HCPEB treatment can refine the surface microstructure of metal, induce the melting of the aluminum matrix on the surface, fill the pores of the material and greatly improve the wear resistance, hardness and other properties [16][17][18][19][20][21]. However, few research works have reported on the effects of electron beams on the electrical conductivity of a treated sample.…”
Section: Introductionmentioning
confidence: 99%